'NOSSO CAMPUS É A CIDADE': UM ESTUDO SOBRE A CONFIGURAÇÃO ESPACIAL DE UM CAMPUS URBANO E SUAS IMPLICAÇÕES SOCIOESPACIAIS1 - Canuto, Robson; Nóbrega, Maria de Lourdes da Cunha; Lima, Andreyna Raphaella Sena Cordeiro de (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
This study aims to investigate space configuration factors that promote patterns of pedestrian movement and social interactions on the campus of the Catholic University of Pernambuco, located in Recife, in the Brazilian State of Pernambuco. The campus consists of four large urban blocks and a number of modern buildings with pilotis, whose configuration facilitates not only pedestrian movement through the urban blocks, but also various other types of activity. The methodology is based on the Social Logic of Space Theory, better known as Space Syntax. The methodology is structured in two parts: (1) Configured Paths, which presents a spatial analysis on two scales (global and local); and (2) Created Paths, which demonstrates pathways established by passers-by. Space Syntax techniques (axial maps of global and local integration) was used to shed light on the nature of pedestrian movement and its social performance. The pilotis were found to play a fundamental role in integrating the city and the campus and are responsible for attracting urban rather than educational activities.